Assessment of cervical involvement in endometrial carcinoma by hysteroscopy and directed biopsy. Issue 1 (1st January 2008) - ÁVila, M. L.; Ruiz, R.; Cortaberria, J. R.; Rivero, B.; Ugalde, F. J.
Abstract : The objective of this study was to assess the diagnostic validity of hysteroscopy and directed biopsy for assessing cervical involvement in endometrial carcinoma. We conducted a study of 240 hysteroscopies and 44 cervical biopsies performed on 240 patients with endometrial carcinoma between 2000 and 2005. Hysteroscopy results suggested cervical involvement in 55 cases, of which only 31 were confirmed (a subtotal hysterectomy was performed in two cases, and the resection margins were examined for tumor invasion). In the 31 patients with confirmed cervical involvement, 19 of the hysteroscopy–directed biopsies were positive, 3 were negative, and 3 provided insufficient material. Six patients did not undergo biopsy. In the 24 patients with hysteroscopy false positive, 10 directed biopsies were positive and 9 were negative. Five patients did not undergo biopsy. Hysteroscopy suggested an absence of cervical involvement in 185 patients. Diagnosis was confirmed in 177 cases, and there were eight false negatives. In our case, office hysteroscopy proved to be a valid means of ruling out cervical involvement in endometrial carcinoma. However, it was not a valid means of detecting tumor involvement, even when combined with directed biopsy.